Ilearning Journal Center Promotion Video Based on Videoscribe Application and Adobe After Effect CC 2015 - Sururi, Ahmad; Sekarwati, Ratna Ayu (SISFOTENIKA, 2021)
Video is a media of information and promotion which is very effective because it has elements of motion, real visualization, images, sounds, and also many elements of music. In the field of promotion and publication, video has become one of the effective and attractive supporting media in its presentation and is considered the most appropriate way to carry out a promotion. The Ilearning Journal Center (IJC) is an innovative electronic journal management system (e-journal) whose application is directed to be able to replace the conventional (printed) journal management system. The purpose of the promotion itself is to introduce the journal learning center to the wider community, especially students and academics, the benefit of this research is to support media information and the promotion ofthe journal learning center. Therefore, the institutuon decides to make a journal in ILearning Journal Center so that institutions want to make a journal in the Ilearning Journal Center. The research method used is the data collection method, namely observation and interviews and research through similar papers in order to get a new idea and better results, with the help of the Videoscribe application and Adobe After Effect, it is expected that informative and effective promotional media can be formed. The purpose of this research is the formation of information and promotion videos so that students and academics can join the ilearning Journal Center and can improve in making a scientific work e-journal or electronically.